2022
DOI: 10.3390/jpm12081254
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Indirect Radiation-Induced Perfusion Change in Fed Vasculature Using Dynamic Contrast CT

Abstract: Recent functional lung imaging studies have presented evidence of an “indirect effect” on perfusion damage, where regions that are unirradiated or lowly irradiated but that are supplied by highly irradiated regions observe perfusion damage post-radiation therapy (RT). The purpose of this work was to investigate this effect using a contrast-enhanced dynamic CT protocol to measure perfusion change in five novel swine subjects. A cohort of five Wisconsin Miniature Swine (WMS) were given a research course of 60 Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 36 publications
5
15
0
Order By: Relevance
“…Vascular atrophy has already been observed in the Group A swine and the direct effects of this atrophy on perfusion were reported previously ( Wuschner et al, 2021a ). Pathological analysis on these swine has confirmed a loss of structure in the vascular wall in addition to reporting additional mechanisms of constriction as well as confirming the intraparenchymal hemorrhage hypotheses reported in ( Wuschner et al, 2021a ), ( Wuschner et al, 2022 ), and ( Marks et al, 2003 ) where vascular leakage was observed as a result of radiation dose delivered ( Wuschner et al, 2021b ).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Vascular atrophy has already been observed in the Group A swine and the direct effects of this atrophy on perfusion were reported previously ( Wuschner et al, 2021a ). Pathological analysis on these swine has confirmed a loss of structure in the vascular wall in addition to reporting additional mechanisms of constriction as well as confirming the intraparenchymal hemorrhage hypotheses reported in ( Wuschner et al, 2021a ), ( Wuschner et al, 2022 ), and ( Marks et al, 2003 ) where vascular leakage was observed as a result of radiation dose delivered ( Wuschner et al, 2021b ).…”
Section: Discussionsupporting
confidence: 72%
“…Frontiers in Physiology frontiersin.org 10 of structure in the vascular wall in addition to reporting additional mechanisms of constriction as well as confirming the intraparenchymal hemorrhage hypotheses reported in (Wuschner et al, 2021a), (Wuschner et al, 2022), and (Marks et al, 2003) where vascular leakage was observed as a result of radiation dose delivered (Wuschner et al, 2021b).…”
Section: Figure 11supporting
confidence: 80%
See 3 more Smart Citations